Hubungan kualitas diet dengan kejadian stunting pada anak 2-5 tahun di Kota Bengkulu - Imelda Sabilla; Betty Yosephin Simanjuntak; Tetes Wahyu (Poltekkes Kemenkes Aceh, 2024)
Background: The quality of children's diet needs attention because it is often low in the nutrients needed to support growth. This means that the practice of poor quality diet given to children will provide an opportunity for stunting to occur.Objective: This study aims to determine the relationship between diet quality and the incidence of stunting in children aged 2-5 years at the Sawah Lebar Community Health Center, Bengkulu City in 2023.Method: Observational research with a cross sectional approach was conducted on 54 mothers of toddlers at the Sawah Lebar Community Health Center, Bengkulu City in May-June 2023. Sampling used a simple random sampling technique. The instrument of this research is the SQ-FFQ (semi quantitative food frequency questionnaire) questionnaire by asking about food ingredients consumed in the past month. Diet quality is divided into 4 categories, namely variety, adequacy, moderation and balance. Diet quality is low if less than ≤60 and height >60. The test used is the chi-square test with a significance level of α=0,05.Results: The results of this study show high levels of varied consumption and low levels of adequacy, moderation and overall balance that the majority (54,7%) have low diet quality. In contrast to the incidence of stunting, it shows that the majority (77,8%) have normal nutritional status (HFA). There is no relationship between diet quality and the incidence of stunting in children aged 2-5 years at the Sawah Lebar Community Health Center, Bengkulu City (p= 0,084).Conclusion: The majority of children have low diet quality, however the majority have normal nutritional status (HFA). The quality of diet in toddlers is not related to the incidence of stunting in children aged 2-5 years at the Sawah Lebar Community Health Center, Bengkulu City.